2017
DOI: 10.1177/1535370217706966
|View full text |Cite
|
Sign up to set email alerts
|

Featured Article: Depletion of HDL3high density lipoprotein and altered functionality of HDL2in blood from sickle cell patients

Abstract: In sickle cell disease (SCD), alterations of cholesterol metabolism is in part related to abnormal levels and activity of plasma proteins such as lecithin cholesterol acyltransferase (LCAT), and apolipoprotein A-I (ApoA-I). In addition, the size distribution of ApoA-I high density lipoproteins (HDL) differs from normal blood. The ratio of the amount of HDL2 particle relative to the smaller higher density pre-β HDL (HDL3) particle was shifted toward HDL2. This lipoprotein imbalance is exacerbated during acute v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 64 publications
0
4
0
1
Order By: Relevance
“…The authors suggested that this was associated with the structural and functional changes seen in the HDL 2 and HDL 3 particles in SCD. As the level of HDL 3 is lowered in SCD, the Apo A1 exchange rate also decreases; thus affecting cholesterol import and export by the HDL particle, which is worsened by the fact that there is an overall reduction in HDL-C levels in patients with SCD [36]. Sexias et al previously suggested that SCD patients with low HDL and relatively increased TG might have a specific dyslipidemic phenotype of the disease [5].…”
Section: Discussionmentioning
confidence: 99%
“…The authors suggested that this was associated with the structural and functional changes seen in the HDL 2 and HDL 3 particles in SCD. As the level of HDL 3 is lowered in SCD, the Apo A1 exchange rate also decreases; thus affecting cholesterol import and export by the HDL particle, which is worsened by the fact that there is an overall reduction in HDL-C levels in patients with SCD [36]. Sexias et al previously suggested that SCD patients with low HDL and relatively increased TG might have a specific dyslipidemic phenotype of the disease [5].…”
Section: Discussionmentioning
confidence: 99%
“…Hypercholesterolemia and Lp-X formation associated with obstructive cholestasis are correlated with an increase in hepatic cholesterol synthesis and are independent of plasma HDL. LCAT is expressed and secreted primarily by the liver and functions in the plasma compartment to catalyze the fatty acid esterification of free cholesterol to form cholesteryl esters, a process important for the maturation of HDL as well as the interconversion of APO B-containing lipoproteins (40,41). All recruited children had normal or low BMI-SDS and Waist-SDS and they did not present with features of metabolic syndrome, thus impact of other external cardiovascular risk factors was diminished.…”
Section: Discussionmentioning
confidence: 99%
“…A point mutation in the beta globin gene results in a dysfunctional red blood cell and leads to the vasculopathy that defines SCD [25]. In SCD patients, cholesterol metabolism appears dysfunctional, as evidenced by abnormal plasma cholesterol, TG, and fatty acid content, in addition to low HDL [25, 26]. To date, there is no well-established consensus among providers on the management of the complications of SCD [27].…”
Section: Discussionmentioning
confidence: 99%